Pengaruh Ekstrak Daun Sirsak (Annona muricata) Terhadap Profil Darah Dan Kelulushidupan Ikan Mas (Cyprinus carpio) Yang Diinfeksi Bakteri Aeromonas hydrophila - Nurjannah, R. Dewi Dharina; Prayitno, Slamet Budi; Sarjito, Sarjito; Lusiastuti, Angela Mariana (Journal of Aquaculture Management and Technology, 2013)
Carp is a freshwater species that is easily cultivated. One of the constraints in cultivating carps (C. carpio) is diseases that ultimately caused mass mortality. The disease that generally affects carp is Motile Aeromonas Septicemia (MAS) caused by Aeromonas hydrophila. Soursop leaves is one of the herbs that can be used as an ingredient to control fish diseases because it contains chemicals that acts bacteriocide. The purpose of this research was to determine the influence and the best dose of soursop leaf extract in feed to the blood profile and survival of carp infected by A. hydrophila. The treatments of this research were addition of soursop leaf extract on feed with 4 different dosages and 3 replicates. The treatments were A (0 g/kg diet), B (5 g/kg diet), C (10 g/kg diet) and D (15 g/kg diet). The result showed that soursop leaf extract in feed of treatment B (5 g/kg diet) significantly different (P0.05) on total erythrocyte (0.83Ã—106 cells/mm3), differential leukocyte include the percentage of monocytes (7.67%), neutrophils (8.67%), lymphocytes (83.67%), phagocytic activity (37%) and survival rate (50%). It can be conclude that soursop leaf extract at dosage 5g/kg was able to stimulate immune response of carp, it was characterized by an increased total leukocytes of carp infected by A. hydrophila.